WOOD COLOR CHANGES BY AMMONIA FUMING - Josip Miklečić, (BioResources, 2012)
This paper studies the influence of ammonia gas on wood color changes in response to an increasing demand for dark colored wood specimens. The darker wood color in ammonia fuming is accomplished through chemical reactions between ammonia gas and wood compounds. We exposed oak, maple, spruce, and larch wood samples to ammonia gas for 16 days. During fuming, the color changes were studied using CIE L*a*b* parameters. After fuming, the changes in extractives content, tannin, and nitrogen content were analyzed. The chemical changes of wood and residues of wood extractives after fuming were analyzed by FTIR spectroscopy. Oak wood reacted intensively with ammonia gas in a very short time, and the darkening was prominent for all the investigated wood species. It was established that tannin had no major influence on color changes of maple and larch wood in the ammonia-fuming process. The FTIR spectra of fumed wood indicated involvement of carbonyl groups, and the FTIR spectra of wood extractives indicated involvement of carbonyl, aromatic, and alcohol groups in reaction with ammonia gas.